Contemporary electromagnetic spectrum reuse techniques: tv white spaces and D2D communications - Carlos Filipe Moreira e Silva (2015)
Over the last years, the wireless broadband access has achieved a tremendous success. With that, the telecommunications industry has faced very important changes in terms of technology, heterogeneity, kind of applications, and massive usage (virtual data tsunami) derived from the introduction of smartphones and tablets; or even in terms of market structure and its main players/actors. Nonetheless, it is well-known that the electromagnetic spectrum is a scarce resource, being already fully occupied (or at least reserved for certain applications). Tra- ditional spectrum markets (where big monopolies dominate) and static spectrum management originated a paradoxal situation: the spectrum is occupied without actually being used! In one hand, with the global transition from analog to digital Television (TV), part of the spectrum previously licensed for TV is freed and geographically interleaved, originating the consequent Television White Spaces (TVWS); on the other hand, the direct communications between devices, commonly referred as Device-to-Device (D2D) communications, are attracting crescent attention by the scientific community and industry in order to overcome the scarcity problem and satisfy the increasing demand for extra capacity. As such, this thesis is divided in two main parts: (a) Spectrum market for TVWS: where a SWOT analysis for the use of TVWS is performed giving some highlights in the directions/actions that shall be followed so that its adoption becomes effective; and a tecno-economic evaluation study is done considering as a use-case a typical European city, showing the potential money savings that operators may reach if they adopt by the use of TVWS in a flexible market manner; (b) D2D communications: where a neighbor discovery technique for D2D communications is proposed in the single-cell scenario and further extended for the multi-cell case; and an interference mitigation algorithm based on the intelligent selection of Downlink (DL) or Uplink (UL) band for D2D communications underlaying cellular networks. A summary of the principal conclusions is as follows: (a) The TVWS defenders shall focus on the promotion of a real-time secondary spectrum market, where through the correct implementation of policies for protection ratios in the spectrum broker and geo-location database, incumbents are protected against interference; (b) It became evident that an operator would recover its investment around one year earlier if it chooses to deploy the network following a flexible spectrum market approach with an additional TVWS carrier, instead of the traditional market; (c) With the proposed neighbor discovery technique the time to detect all neighbors per Mobile Station (MS) is significantly reduced, letting more time for the actual data transmission; and the power of MS consumed during the discovery process is also reduced because the main processing is done at the Base Station (BS), while the MS needs to ensure that D2D communication is possible just before the session establishment; (d) Despite being a simple concept, band selection improves the gains of cellular communications and limits the gains of D2D communications, regardless the position within the cell where D2D communications happen, providing a trade-off between system performance and interference mitigation.